Use of a radial artery 'slender' sheath for facilitating transfemoral arterial access for neuroendovascular embolization in a very young infant. Issue 3 (June 2019) - Miao, Timothy L; Figueroa, Enriqueta Lucar; Bajunaid, Khalid; Mayich, Michael; de Ribaupierre, Sandrine; Pandey, Sachin K
Pediatric neuroendovascular procedures are increasingly performed as several studies have shown the safety of these interventions. In the literature, an upper limit of 4 French catheter size is conventionally used for femoral access in neuroangiography of very young infants. However, this constraint in luminal size may not allow for more complex procedures. We present the previously unreported use of a radial 5 French slender catheter with ultrathin walls for femoral access for aneurysm embolization in a 3-month-old boy presenting with left M2 aneurysm rupture.